CLINICAL RESULTS OF PERCUTANEOUS TREATMENT IN ACUTE MYOCARDIAL INFARCTION DUE TO LEFT MAIN CORONARY ARTERY STENOSIS - Bojović, Dijana; Mehmedbegović, Zlatko (Medicinski podmladak, 2024)
Introduction: Acute myocardial infarction due to left main coronary artery stenosis is rare, but catastrophic event often accompanied by sudden cardiac death and/or cardiogenic shock. The optimal revascularization strategy for unprotected left main coronary artery disease is the subject of ongoing debate, especially in urgent settings, where immediate optimal acute angiographic result is required to ensure patient survival and improve prognosis. Aim: The aim of this study is to investigate patient characteristics, procedural and clinical variables associated with favorable outcomes of percutaneous treatment. Material and Methods: We retrospectively reviewed 40 patients undergoing PCI with acute myocardial infarction due to left main coronary artery stenosis between 1st January 2019 and 21st December 2022. Results: There was a total of 40 patients with mean age of 70.83±11.415. Cardiogenic shock occurred in 20 (50%) patients. Two patients (5%) died in the catheterization laboratory and 16 (40%) died during hospitalization. 22 patients survived to be discharged; five patients died during the follow-up period. The overall mortality rate was 23 (57.5%). Factors associated with increased mortality included female gender (p=0.008), cardiogenic shock (p=0.025) and inotropes (p=0.000). Conclusion: Acute myocardial infarction caused by left main coronary artery stenosis is complicated by high incidence of cardiogenic shock and mortality. In univariate analysis, cardiogenic shock, female gender and usage of inotropes correlated with death. Emergency PCI provides an important treatment option in these high-risk patients, but mortality remains high. Keywords: acute myocardial infarction; percutaneous coronary intervention; left main coronary artery